Myrinia pulvinata (Wahlenb.) Schimp. (Amblystegiaceae) — новий вид і рід для бріофлори України - Барсуков, О.О.; Вірченко, В.М. (Український ботанічний журнал, 2012)
Сообщается о находке Myrinia pulvinata (Wahlenb.) Schimp. (Amblystegiaceae, Bryophyta) — нового вида и рода для Украины. Он был обнаружен на стволе липы в зеленом насаждении г. Харькова (юго-восток Украины, 49°57′39″ с.ш., 36°19′19″ в.д.). Обсуждаются его экология, распространение и таксономическое положение. Myrinia pulvinata (Wahlenb.) Schimp. (Amblystegiaceae, Bryophyta) is reported for the first time for Ukraine. It was found on a trunk of Tilia cordata in the green plantation of Kharkiv city (SE Ukraine, 49°57′39″N — 36°19′19″E). Peculiarities of ecology, distribution and taxonomic position of the species are discussed.